Statistics for nursing : a practical approach - Heavey, Elizabeth (Burlington, MA : Jones & Bartlett Learning, 2024)
'Today's nurse faces even more questions about understanding and interpreting data. Although statistics has not changed in its essence, nurses are leveraging new technologies to interpret data in the clinical space. Understanding how to use that information and make successful clinical decisions are the essence of the role of the nurse. The 4th edition will provide new research and highlight an unfolding case study that is used throughout the text to connect concepts to situations, equipping students and instructors with the right tools to leverage the data in a safe and accurate way'--
Introduction to statistics and levels of measurement -- Presenting data -- Descriptive statistics, probability, and measures of central tendency -- Measuring data -- Sampling methods -- Generating the research idea -- Sample size, effect size, and power -- Chi-square -- Student t-test -- Analysis of variance (ANOVA) -- Correlation coefficients -- Regression analysis -- Relative risk vs. absolute risk and other public health measures you commonly see.
'EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA.' Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on print version record.
Includes online access.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 050
Keywords: Nursing -- Statistical methods; Statistics